Nicotine and periodontal tissues - Malhotra Ranjan; Kapoor Anoop; Grover Vishakha; Kaushal Sumit (Wolters Kluwer Medknow Publications, 2010)
Tobacco use has been recognized to be a significant risk factor for the development and progression of periodontal disease. Its use is associated with increased pocket depths, loss of periodontal attachment, alveolar bone and a higher rate of tooth loss. Nicotine, a major component and most pharmacologically active agent in tobacco is likely to be a significant contributing factor for the exacerbation of periodontal diseases. Available literature suggests that nicotine affects gingival blood flow, cytokine production, neutrophil and other immune cell function; connective tissue turnover, which can be the possible mechanisms responsible for overall effects of tobacco on periodontal tissues. Inclusion of tobacco cessation as a part of periodontal therapy encourages dental professionals to become more active in tobacco cessation counseling. This will have far reaching positive effects on our patients′ oral and general health.